Peningkatan Ekonomi Masyarakat Melalui Pelatihan Tali Kur di Desa Basseang, Kecamatan Lembang, Kabupaten Pinrang - Jusmawandi, Jusmawandi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
People are left behind not only because of limited infrastructure facilities but also because of the economy. The progress of a region is in line with the policies initiated to bring about changes in people's lives for the better. In the Very Disadvantaged Village community, skills training can make the community creative so that it is expected to have an impact on improving the community's economy. The skill of stringing ropes into an economical product is one way to increase people's income. However, the lack of strategies and means and facilities need support in realizing business success. The community service method used in this activity is the lecture and practice method. The number of participants involved were 21 people who were divided into four groups. Each group received guidance from the trainer starting from theory and assembling techniques. The materials and tools used are purchased at the central market of Pinrang Regency. The trainers involved are people who have skills in stringing ropes. The end of this training shows that participants can make a work in the form of a bag. This bag has a unique shape and can attract customers. Participants also received promotional strategy materials on social media so that their work could be marketed. The training lasted for two days which was attended by a group of women in Passaparang Village, Basseang Village, Pinrang Regency. The post-training commitment brought that participants agreed to continue this knitting business in order to improve individual skills.